Zoraida: A Romance of the Harem and the Great Sahara - Le Queux, William, 1864-1927; Piffard, Harold, 1867-1938 (Salt Lake City, UT : Project Gutenberg, 2012)
"Zoraida: A Romance of the Harem and the Great Sahara" by William Le Queux is a novel written in the late 19th century. The narrative is set against the backdrop of the Sahara Desert and follows the adventures of Cecil Holcombe, an Englishman who becomes embroiled in the culture and intrigue of the region. The book explores themes of love, danger, and the clash between Western civilization and Eastern mystique, particularly through the enigmatic character of Zoraida, a woman who plays a pivotal role in Holcombe's journey. The opening of the novel introduces Cecil Holcombe as he traverses the harsh landscape of the Sahara in search of a caravan headed to the Touat Oasis. We learn of his severe trials in the desert, including a dangerous attack by marauders that decimates his companions, leaving him as the sole survivor. The tension escalates when he encounters Ali Ben Hafiz, a merchant who takes him under his protection. As the chapter progresses, Ali shares his ominous views on love and superstition, foreshadowing a significant event in Holcombe's life regarding the beautiful and mysterious Zoraida, who later becomes the focal point of his fate. The opening effectively sets the stage for a tale of adventure, intrigue, and prophetic warnings about love in a world steeped in tradition and danger. (This is an automatically generated summary.)
Release date is 2012-10-09
Produced by Nick Hodson of London, England
Keywords: Spy stories; Sahara -- Fiction; Harems -- Fiction